Management consultancy: Boundaries and knowledge in action - STURDY, Andrew (Institutional Knowledge at Singapore Management University, 2009)
Drawing on a three‐year, in‐depth, ‘fly‐on‐the‐wall’ study of client‐management consultant interactions, knowledge flow in management consultancy projects is shown to be mediated by multiple and shifting boundaries or ‘insider‐outsider’ relationships. This challenges dominant assumptions about management consultancy as being either a source of new ideas and processes or simply the legitimation of client knowledge. Rather, different actors, roles, and types of knowledge are involved in an interactive and dynamic process where various boundaries are constructed, reinforced, negotiated, and transformed. The chapters selectively explore these dynamics, revealing the importance of boundary complexity; the role of humour and challenge in often tense relationships; and the importance of shared knowledge domains such as sector knowledge. They are based upon a model of client-consultant relationships developed from theories of knowledge and social boundaries. A wide range of consultancy contexts are covered, including: a US‐based strategy firm and a multinational client; the public and private sectors; a sole practitioner consultant; and IT implementation in financial services. These have a wider significance in terms of our understanding of project working, innovation/change, inter-organizational relations and professional and business services.